Diagnóstico comunitario de salud del Barrio Motupe Bajo Sector VI, septiembre-diciembre de 2013 - Cárdenas Veintimilla, María Fernanda (2013)
This research 's main objective is to help strengthen the INTEGRAL MODEL SYSTEM WARNING NATIONAL COMMUNITY FAMILY HEALTH Intercultural E at the University Hospital of Motupe , providing statistics and data that enable basic health teams - EAIS ( Care Teams Integral health ) formulate local health proposals , aimed at improving the quality of life of the community " Under Motupe Sector VI " . This research is descriptive , in which facts and characteristics related to population and environment are detailed , the universe consisted of 67 families and 274 inhabitants , to collect information about the family record compiled by the MSP was used and an annex to this document , the form of interview allowed complete information besides obtaining data that will serve as a baseline for future research are discussed . The most relevant data of this research include the female population prevails , education remains at the Basic level plus five illiterate some of whom are heads of households were found , few school children and adolescents identified the which most of them study in regard to sexually active women , the rhythm method is the most widely used family planning. Regarding the epidemiological profile include the Hypertension is prevalent chronic disease , affecting the population between the ages of 20 and 64, and in relation to a child with disabilities both physical and intellectual disabilities 100 % identified . Research bibliography and appendices which involves the development of it is supported. Keywords : Community health diagnosis Motupe Barrio Bajo Sector VI and results.